2020
DOI: 10.1007/s12553-020-00413-w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the retinal changes of the 3×Tg-AD mouse model of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder whose diagnosis remains a notable challenge. The literature suggests that cerebral changes precede AD symptoms by over two decades, implying a significantly advanced stage of AD by the time it is usually diagnosed. In the study herein, texture analysis was applied to computed optical coherence tomography ocular fundus images to identify differences between a group of the transgenic mouse model of the Alzheimer's disease (3×Tg-AD) and a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on OCT imaging, retinal changes induced by neurodegenerative diseases have been found, including changes in retinal layer thickness (Cunha et al, 2016 ; Song et al, 2020 ; Salobrar-García et al, 2021 ). Recently, we have also shown that retinal texture biomarkers can help discriminate between age-matched healthy controls and animal models of Alzheimer's disease (AD) in the early stages (Nunes et al, 2019 ; Ferreira et al, 2020 , 2022 ; Guimarães et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on OCT imaging, retinal changes induced by neurodegenerative diseases have been found, including changes in retinal layer thickness (Cunha et al, 2016 ; Song et al, 2020 ; Salobrar-García et al, 2021 ). Recently, we have also shown that retinal texture biomarkers can help discriminate between age-matched healthy controls and animal models of Alzheimer's disease (AD) in the early stages (Nunes et al, 2019 ; Ferreira et al, 2020 , 2022 ; Guimarães et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This results in a total of 80 features (20 features × 4 quadrants) per layer (5) per acquisition time point (7), which were then subjected to feature selection (described in Statistical Analysis). Further details on the feature extraction process can be found in (21).…”
Section: Texture Featuresmentioning
confidence: 99%